Short Communication: Leopard cat (Prionailurus bengalensis) distribution in the Cisokan Hydropower Plant, West Java, Indonesia - Teguh Husodo; Erri Noviar Megantara; Asep Zainal Mutaqin; Dwi Rustam Kendarto; Indri Wulandari; Sya Sya Shanida (Society for Indonesian Biodiversity, 2022)
Abstract. Husodo T, Megantara EN, Mutaqin AZ, Kendarto DR, Wulandari I, Shanida SS. 2022. Short Communication: Leopard cat (Prionailurus bengalensis) distribution in the Cisokan Hydropower Plant, West Java, Indonesia. Biodiversitas 23: 6247-6253. Globally, leopard cats (Prionailurus bengalensis) can be found in various land cover types. Information about leopard cats is still low in Indonesia, especially in Java. Java Island has high human activities that impact leopard cats, such as the UCPS hydropower development area, a non-conservation area. The UCPS hydropower plant is in the upper catchment area of ??the Cisokan River as a tributary of the Citarum River. Although leopard cats can adapt to various land cover types, monitoring their existence is necessary. This study aims to reveal the distribution of leopard cats in the UCPS hydropower development area, Cianjur Regency and West Bandung Regency, West Java, Indonesia. Sign survey and literature were applied in this study. Fifty-eight leopard cat findings were found in the UCPS hydropower area. Leopard cats were found in 16 of the 47 grids from 2012-2022. After 5-10 years, leopard cats still use the same area in certain areas to meet their needs.In eight of 16 grids, 50% of the grids used by leopard cats were habitats used repeatedly. They were most commonly found in shrubs (39%), riparian (20%), and pine plantations (15%). Leopard cats were located at 445-895 masl and are most commonly found at 400-800 masl. Leopard cats are found in the UCPS development area and Perhutani Land. After 5-10 years, leopard cats still use the UCPS development area, so the habitat still fulfills their daily needs. Further monitoring is needed to determine the ecological status of the leopard cat population during the construction and post-construction process.